Nutritional quality assessment of commonly sold steamed bambara groundnut (Vigna subterranea L. Verdc) pastes in Lafia motor parks, Nasarawa state, Nigeria - Aremu, MO; Yashim, TC; Ibrahim, H; Adeyeye, EI; Omosebi, MO; Ablaku, BE (Bangladesh Journal of Scientific and Industrial Research, 2022)
The proximate, amino acid, and mineral compositions of commonly sold steamed bambara groundnut pastes in two different motor parks (SBGM and SBGJ) were investigated using standard procedures and methods. The respective proximate composition values (g/100g sample) of SBGM and SBGJ were: moisture (3.02 and 3.57), ash (7.13 and 7.69), crude fat (14.98 and 18.94), crude protein (21.46 and 19.34), crude fibre (5.90 and 7.34), and carbohydrate by difference (47.53 and 43.14). The most abundant minerals in the samples were potassium (219.63 and 232.86 mg/100g), followed by sodium (164.25 and 158.41 mg/100g). The amino acid profile of the proteins revealed that both samples contained nutritionally beneficialquantities of most essential amino acids. The total essential amino acid (TEAA) (with His) was 42.89 and 45.08g/100g for SBGM and SBGJ samples, respectively. The calculated isoelectric point (pI) and predicted protein efficiency ratio (P-PER) for the samples were (4.22 and 5.18) and (2.08 and 2.45). Valine was the first limiting amino acid in both samples. Bangladesh J. Sci. Ind. Res. 57(1), 27-40, 2022